2009
DOI: 10.1007/s12016-009-8162-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin in Lupus Panniculitis

Abstract: Systemic lupus erythematosus (SLE) is a disease of unknown cause that may involve one or many organ or systems. Skin involvement is a major feature in this disease, and a wide variety of skin conditions may be present. Lupus erythematosus panniculitis (LEP) constitutes a rare form of cutaneous lupus characterized by recurrent nodular or plaque lesions that can vary from a benign and mild course to a more disfiguring disease. Initial therapy includes corticosteroids, antimalarials, and azathioprine and, in refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 64 publications
(73 reference statements)
0
20
0
Order By: Relevance
“…Injections of glucocorticosteroid medications into lesional areas are generally ineffective and can exacerbate the atrophy (Fraga and García-Díez, 2008). Systemic, first-line therapy for LEP as well as other forms of CLE traditionally has been antimalarial medications such as hydroxychloroquine (dose 200-400 mg daily) or chloroquine (250-500 mg daily) (Bednarek et al, 2015, Espírito Santo et al, 2010, Housman et al, 2003). Systemic corticosteroid medications are often useful for severe cases that are accompanied by SLE (Bednarek et al, 2015, Espírito Santo et al, 2010).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Injections of glucocorticosteroid medications into lesional areas are generally ineffective and can exacerbate the atrophy (Fraga and García-Díez, 2008). Systemic, first-line therapy for LEP as well as other forms of CLE traditionally has been antimalarial medications such as hydroxychloroquine (dose 200-400 mg daily) or chloroquine (250-500 mg daily) (Bednarek et al, 2015, Espírito Santo et al, 2010, Housman et al, 2003). Systemic corticosteroid medications are often useful for severe cases that are accompanied by SLE (Bednarek et al, 2015, Espírito Santo et al, 2010).…”
Section: Treatmentmentioning
confidence: 99%
“…Other reported systemic therapies include thalidomide (Housman et al, 2003, Espírito Santo et al, 2010), dapsone (Espírito Santo et al, 2010, Ujiie et al, 2006), methotrexate (Espírito Santo et al, 2010, Grossberg et al, 2001), cyclosporine (Espírito Santo et al, 2010, Saeki et al, 2000, Wozniacka et al, 2007), cyclophosphamide (Espírito Santo et al, 2010, Grossberg et al, 2001), intravenous immunoglobulins (Espírito Santo et al, 2010), and rituximab (McArdle and Baker, 2009, Moreno-Suárez and Pulpillo-Ruiz, 2013). …”
Section: Treatmentmentioning
confidence: 99%
“…Therapy strategies for LEP involving IVIG are based on single case reports [4, 11, 12]. The patient received immunoglobulins (Sandoglobulin P) in the initial pulse of 2 g/kg of body weight, in combination with oral steroids and antimalarials, followed by 400 mg/kg body weight IVIG pulses at monthly intervals for a maximum of 6 months, in accordance with the regime reported by Goodfield et al [11].…”
mentioning
confidence: 99%
“…Terms LEP and lupus profundus were used interchangeably, however it is suggested that the term “lupus profundus” should be used when the subcutaneous inflammatory process is accompanied by overlying lesions typical for discoid lupus erythematosus (DLE) [4]. The LEP occurs more frequently in adult women.…”
mentioning
confidence: 99%
See 1 more Smart Citation